The hows of masculinity an analysis of the masculinities performed by Daniel Padilla in The Hows of Us, the House Arrest of Us and Mabagal - Gabriel, Adryen Elysses Bringas 1999
The Hows of Masculinity looked into the gender performances of Daniel Padilla in three different texts: The Hows of Us, The House Arrest of Us, and Mabagal. The characters portrayed by Daniel Padilla are this study's main units of analysis. This study particularly explored the different gendered images he presented in the texts, including stereotypes, ideals, and issues on gender and sexualities. Through a textual analysis, I analyzed the internal and external characteristics of his characters that were explicitly mentioned and implicitly presented in the texts, as well as his relationships with the other characters, specifically those portrayed by Kathryn Bernardo. Guided by the scholarship of Judith Butler (1993) on gender performativity, Raewyn Connell & James Messerschmidt's (2005) concepts on rethinking hegemonic masculinity, and Rolando Tolentino's (2000) insights on the myth of masculinity, I identified the different masculinities of Daniel Padilla and examined how his characters challenge the dominant or hegemonic type of masculinity.